GGenetics in Czech Biology Textbooks: History and Current Perspective - Machová, Markéta (Scientia in educatione, 2021)
History of genetics begins at the end of 19th century, which makes it very young science field among other subdisciplines of biology. Therefore, it is possible to analyse both its evolution as a science and its growth as educational content in compulsory education. The main witnesses of this transformation, which are still accessible today, are biology textbooks. Curricular changes relating to genetics unfortunately differed between western and former Eastern Bloc countries due to the ideological impact on both science and education, with the Communist ideology largely undermining the relevance of genetics. On the other hand, the present-day Czech educational system may accentuate the relevance of genetics, yet there has been no broader analysis as to how and to what extent education might have been modified, nor how long it took to re-establish genetics in the curriculum. This work shows that even though the content of genetics was rehabilitated in textbooks and curriculum already in the 1980s, the current presentation of genetics in textbooks is still problematic. Content of textbooks related to genetics lacks coherence and it is scattered throughout several different grades. The information is not sufficiently interconnected with related topics (such as reproduction and evolution) and has not been incorporated into a coherent and logical system that both students and teachers could navigate (mainly due to unclear explanation of formation of characteristics via process of gene expression).